A PROFILE OF THE NORTHAMPTON MINORITY - McCleery, Jennifer Reagan (2017)
Jonathan Edwards was famously dismissed from the Northampton church in 1750. On June 22 of that year, the male members of the Northampton church voted by an overwhelming majority to sack him, their arms going up, as witnessed by neighboring minister Robert Breck, as if “on springs.” But no matter how great the resentment of him,Edwards did not, could not depart from town immediately. Rather, he lingered for some months, trying to make arrangements for his next position, seeking to sell his house and property, and perhaps, most awkwardly, providing pulpit supply while the church searched for a new minister.
2 Appendices
Keywords: American Religious History; Northampton